Variation of faecal calprotectin level within the first three months after bowel resection is predictive of endoscopic postoperative recurrence in Crohn's disease. Issue 7 (July 2020) - Boube, Mathilde; Laharie, David; Nancey, Stéphane; Hebuterne, Xavier; Fumery, Mathurin; Pariente, Benjamin; Roblin, Xavier; Peyrin-biroulet, Laurent; Minet-quinard, Régine; Pereira, Bruno; Bommelaer, Gilles; Buisson, Anthony; et al.
Abstract: Background: Early prediction of postoperative recurrence (POR) remains a major concern in Crohn's disease (CD). Aims: To assess serial faecal calprotectin (Fcal) monitoring within the first three months to predict CD endoscopic POR. Methods: In a multicenter randomized controlled trial, CD patients received azathioprine 2.5 mg/kg/day with oral curcumin (3 g/day) or placebo. Fcal was measured at baseline, one month (M1) and M3. Endoscopic POR at M6 was defined as Rutgeerts' index ≥ i2b (central reading). Results: Among the 48 patients included, there was no significant difference of median Fcal levels at baseline ( p  = 0.15), M1 ( p  = 0.44) and M3 ( p  = 0.28) between patients with or without endoscopic POR at M6. Fcal kinetics during the first 3 months after surgery was significantly different between the patients with or without POR at M6 ( p  = 0.021). The median variation between Fcal level at baseline and M3 (ΔFcal M3–M0) was significantly higher in patients with endoscopic POR compared to those without POR ( p  = 0.01). ΔFcal M3–M0 >+10% demonstrated the best performances to predict endoscopic POR at M6 (AUC=0.73, sensitivity=64.7%[41.1–82.7], specificity=87.5%[68.0–96.3], negative predictive value=77.8%[57.5–91.4] and positive predictive value=78.6%[49.2–95.3]). Conclusion: Fcal variation within the first three months after ileocolonic resection is a promising predictor of early endoscopic POR in CD patients.